Macular vasculature, visual acuity, and irreversibly sickled cells in homozygous sickle cell disease. - Marsh, R J (1982)
Observations of visual acuity and the conjunctival, macular, and perimacular vascularity have been assessed in patients with homozygous sickle cell (SS) disease. There were 17 matched pairs, each consisting of one patient with a high count (greater than or equal to 15%) and one with a low count (less than or equal to 5%) of irreversibly sickled cells (ISCs). The macular vascular bed was assessed by measurements of the foveal avascular zone (FAZ), perimacular avascular zones, and counts of perimacular vascular abnormalities (perimacular counts). Small foveal avascular zones and high perimacular counts were commoner in younger than older patients and there was a significant inverse correlation between size of the FAZ and the perimacular count. These observations were compatible with the hypothesis that perimacular vessel anomalies represent the early vaso-occlusive phase which progresses to ischaemia and the formation and enlargement of avascular areas. Visual acuity was assessed by Snellen's test type and by measuring contrast sensitivity. There was no obvious relationship between acuity measured by the 2 methods and no relationship between acuity and observations of macular vascularity. High ISC counts were significantly related to abnormalities of the conjunctival vasculature, but no relationship was noted with abnormalities of the macular vasculature or with visual acuity.